2015
DOI: 10.1016/j.phrp.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Characteristics of Infrequent and Frequent Outpatients Visiting Korean Traditional Medical Facilities

Abstract: ObjectivesThis study was intended to analyze the characteristics of infrequent and frequent outpatients visiting Korean medical facilities, and find the related variables of frequent users.MethodsThe data source was the Report on the Usage and Consumption of Korean Medicine (2011) published by the Ministry of Health and Welfare and Korea Institute for Health and Social Affairs. We analyzed outpatient data using SAS 9.2.ResultsAs much as 46.6% of the patients used Korean medical services over 11 times in 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
6
1
Order By: Relevance
“…This study indicated that the main reason for these findings and the differences from the results of the previous study was the recent increase in the use of KM and KM&WM as CT among elderly individuals [ 20 , 21 , 22 ]. Therefore, we investigated the social, policies, economic and scientific causes based on the above research results.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This study indicated that the main reason for these findings and the differences from the results of the previous study was the recent increase in the use of KM and KM&WM as CT among elderly individuals [ 20 , 21 , 22 ]. Therefore, we investigated the social, policies, economic and scientific causes based on the above research results.…”
Section: Discussioncontrasting
confidence: 72%
“…Finally, from a scientific aspect, the effectiveness of KM is increasingly demonstrated with scientific evidence. Consequently, the public interest in CT has also increased [ 20 ]. A recent study on CT based on an analysis of 24 case reports indicated that diseases of the nervous system were the most likely to be treated with CT due to its excellent treatment effects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [7, 8], elderly people tended to visit TKM institutions more frequently than younger people. However, age was not a factor that affected taking herbal medicines in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…This study described the basic characteristics of those who had taken herbal medicines and those who had not taken them, the places that herbal medicines were purchased, the reasons for taking or not taking herbal medicine, and adverse events experienced due to herbal medicines and how the adverse events were addressed. In previous studies [ 7 , 8 ], elderly people tended to visit TKM institutions more frequently than younger people. However, age was not a factor that affected taking herbal medicines in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…There is a survey using data from the 2011 Korean Ministry of Health and Welfare’s Report (KMOH’s Report) on the Usage and Consumption of Korean Medicine in South Korea. It reported that the percentage of Korean medicine users who answered that their subjective health level was "bad" or "very bad" was greater in frequent users who used ≥ 11 times in a period of 3 months compared to non-frequent users (≤ 3 times) [ 7 ]. However, in Korea, China, and Taiwan, acupuncture is a part of traditional medicine, and the survey focused on the use of traditional medicine in general (including herbal medicine), not specifically acupuncture use.…”
Section: Introductionmentioning
confidence: 99%